2013
DOI: 10.1002/2013ja019179
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotail structure of the giant magnetospheres: Implications of the viscous interaction with the solar wind

Abstract: [1] The internal sources of plasma in the giant magnetospheres of Jupiter and Saturn affect magnetospheric dynamics in terms of magnetosphere-ionosphere coupling and auroral current systems, as well as the interaction with the solar wind. The radial transport of plasma at Jupiter is well constrained to vary between 300 kg/s and 1200 kg/s over timescales of 20-60 days. Saturn's neutral-dominated inner magnetosphere has presented a challenge for determining the radial mass transport rates with values ranging bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 83 publications
4
39
1
1
Order By: Relevance
“…The above scenario assumes plasma to continue accumulating during the quiescent period of several days to weeks; i.e., the Jovian magnetosphere can hold a correspondingly large amount of plasma. Furthermore, the radial plasma mass transport rate also depends on the solar wind [Delamere and Bagenal, 2013]. The radial transport speed is fast in the outer magnetosphere, and it depends on radial profiles of density, magnetodisc scale height, and the radial plasma mass transport rate [Bagenal and Delamere, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above scenario assumes plasma to continue accumulating during the quiescent period of several days to weeks; i.e., the Jovian magnetosphere can hold a correspondingly large amount of plasma. Furthermore, the radial plasma mass transport rate also depends on the solar wind [Delamere and Bagenal, 2013]. The radial transport speed is fast in the outer magnetosphere, and it depends on radial profiles of density, magnetodisc scale height, and the radial plasma mass transport rate [Bagenal and Delamere, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic flux circulation is also a possible auroral brightening mechanism [Delamere and Bagenal, 2013;Delamere et al, 2015]. Delamere and Bagenal [2013] proposed that the solar wind compression enhances transport of dayside closed magnetic flux to the nightside and subsequent tail reconnection.…”
Section: Discussionmentioning
confidence: 99%
“…Notice that the estimate is based on a conservative transport rate and may therefore be larger. Earlier mass loading rate estimates have ranged from ∼28 kg/s [ Liu et al , ] and 20–50 kg/s [ Delamere and Bagenal , ] to 100 kg/s [ Pontius and Hill , ] and a net mass outflow rate of ∼280 kg/s [ Chen et al , ], with several mass loading rate estimates ranging from 100 to 150 kg/s [e.g., Pontius and Hill , ]. The estimated plasma mass loading rate can be compared with estimations of the neutral mass loading rate from Enceladus that ranges from ∼36–72 kg/s for flyby E2 [ Smith et al , ] to ∼1600 kg/s for flyby E0 [ Saur et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively to solar wind driven reconnection, the viscous interaction of the solar wind with the planetary magnetosphere, which involves magnetic reconnection on a small scale (Delamere & Bagenal 2013), influences Saturn's magnetopause dynamics. Cassini UVIS observations revealed recently the presence of small-scale structures in the dayside main auroral emissions indicative of magnetopause KelvinHelmholtz instabilities, which are key elements of the solar wind-magnetosphere viscous interaction .…”
Section: Solar Wind Effects On the Auroramentioning
confidence: 99%
“…It has been suggested that Saturn's magnetotail is influenced by a combination of solar wind (Dungey 1961, like at Earth) and internally driven magnetic reconnection (Vasyliunas 1983) as well as viscous interaction of the solar wind with the planetary magnetosphere (Delamere & Bagenal 2013). Tail reconnection in the Dungey-cycle manner is expected to result in bright and fast rotating aurorae, which expand poleward in the dawn sector, reducing significantly the size of the polar cap and thus resulting in the closure of flux (Badman et al 2005;Jia et al 2012).…”
Section: Solar Wind Effects On the Auroramentioning
confidence: 99%